Systematic review: quality of trials on the symptomatic effects of the low FODMAP diet for irritable bowel syndrome. Issue 12 (25th April 2017) - Krogsgaard, L. R.; Lyngesen, M.; Bytzer, P.
Summary: Background: The low Fermentable Oligo‐, Di‐ Monosaccharides, and Polyoles (FODMAP) diet is a new treatment option for irritable bowel syndrome (IBS). Experts refer to the diet as supported by high level of evidence, but an evaluation of the quality of trials is lacking. Aim: To provide a systematic review of the quality of trials on the symptomatic effects of the low FODMAP diet for IBS. Methods: Pubmed and EMBASE were searched for randomised controlled trials (RCTs) reporting effect of the low FODMAP diet on IBS symptoms. The quality of trials was evaluated by estimating risk of bias and assessing trial methodology. Results: Nine RCTs were eligible, including 542 patients. The intervention period was from 2 days to 6 weeks and one trial included a 6‐month follow‐up. Three trials intervened by providing meals, controlling with a diet high in FODMAP content. In six trials, the intervention was instruction by a dietician and a variety of control interventions were used, all with limited established efficacy. Domains with a high risk of bias were identified for all the trials. High risk of bias dominated domains regarding blinding, with only one trial double‐blinded. Conclusions: The RCTs on the low FODMAP diet are characterized by high risk of bias. The diet has not been studied in a randomised, controlled setting for more than 6 weeks and trials examining the effect of the important reintroduction period are lacking. There is a risk that the symptomatic effects reported in the trials are driven primarily by a placebo response. Abstract : Linked Content This article is linked to Quigley paper. To view this article visithttps://doi.org/10.1111/apt.14140 .